Exploration of the government officials' interference on the editorial independence of South African Broadcasting Corporation - Ramogale, Peter Thabo (My University, 2023)
Public media broadcasting exists in the world as an advocate of society in all aspects of life globally. Public media broadcasting is provided in many ways, such as television, radio, online, and social media platforms. Public media broadcasting accommodates all types of audiences regardless of their conditions and disability status. The research explored the government officials’ interference in the editorial independence of the South African Broadcasting Corporation (SABC). Audiences use public media broadcasting entities to be informed and educated about social, economic, and political issues, as well as the ability to deliver critical information freely to citizens and protect people’s human rights at an affordable cost. Public broadcasting entities such as the South African Broadcasting Corporation (SABC) greatly impact how citizens view and analyse societal activities and incidents in day-to-day operations. The research objectives are to assess the implementation of the SABC’s news editorial policy, to examine the alleged editorial interference of the SABC on the public and to establish the effects of editorial interference of the SABC on the public. The research utilised agenda-setting theory and Authoritarian theory, which show an interlinked relationship between media, authorities, and media agenda. The study analysed various literature, which aligns with the study's aim and objectives. The qualitative approach method was utilised in the study, and it yielded outcomes retrieved through textual analysis and focus group discussion. Textual analysis and reflexive thematic analysis were used to analyse the collected data. The population utilised as a sample were online news articles that reported on the alleged editorial interference at the SABC and audiences that are utilising SABC platforms to receive and access news and information. Textual analysis of the online news articles' findings reveals that the SABC has experienced activities of editorial interference by government officials, primarily politicians who abused their power to pass their agenda to society via SABC platforms. Furthermore, focus group findings show that participants have strong beliefs supported by incidents/events that they provided as examples of SABC experiencing editorial interference by government officials. Keywords: SABC, Audience, Government, Editorial, Entities, Officials, Broadcasting, Public.
Thesis (M. A. (Media Studies)) -- University of Limpopo, 2023
Keywords: SABC; Audience; Government; Editorial; Entities; Officials.; Broadcasting.; Public; Interference (Perception); Broadcasting policy; Mass media -- South Africa